2001
DOI: 10.1248/bpb.24.1420
|View full text |Cite
|
Sign up to set email alerts
|

Trichorzin HA V, a Member of the Peptaibol Family, Stimulates Intracellular cAMP Formation in Cells Expressing the Calcitonin Receptor.

Abstract: By a cell-based screening of an in-house natural product library, trichorzin HA V, belonging to a peptaibol family, was isolated from a strain of fungus Trichoderma as a calcitonin (CT) agonist. Like CT, trichorzin HA V elevated cAMP levels in T47D cells which endogenously express the human CT receptor. It also stimulated cAMP formation in cells expressing recombinant human CT receptor, but not in those that do not express the receptor, suggesting that it selectively interacts with the CT receptor. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Csermely Katayama et al, 2001;Peltola et al, 2004). However, the antimicrobial mechanisms of peptaibols are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Csermely Katayama et al, 2001;Peltola et al, 2004). However, the antimicrobial mechanisms of peptaibols are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on peptaibols has focused on their biosynthetic pathways, conformational properties and amino acid sequences (Benedetti et al, 1982;Wiest et al, 2002). It has also been reported that peptaibols promote the inhibition of mitochondrial ATPase, uncoupling of oxidative phosphorylation, immunosuppression, inhibition of platelet aggregation and induction of fungal morphogenesis (Shima et al, 1990;Matsuzaki et al, 1991;Csermely et al, 1994;Katayama et al, 2001;Peltola et al, 2004). However, the antimicrobial mechanisms of peptaibols are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As therapeutic agents they inhibit the envelope replication of viruses such as influenza A, vesicular stomatitis virus, and HIV; they promote wound healing; they inhibit the formation of peptide β-amyloid in cultured cells from the cerebral cortex of pigs; and they may have an important role in neurodegenerative diseases (Degenkolb et al, 2008). Peptaibols have a mechanism of action similar to calcitonin, a hormone secreted by the thyroid gland in response to elevated levels of calcium in the blood that plays an important role in maintaining homeostasis (Katayama et al, 2001). Experiments with peptaibols demonstrate their ability to induce the secretion of catecholamines from chromaffin cells in the adrenal medulla by calcium influx; to activate adenylate cyclase and guanylate cyclase; to make the plasma membrane of mouse lymphocytes permeable to ATP, thereby allowing the adenylate cyclase activity of the cells to be determined; and to exert antitumor effects in hepatocellular carcinoma cells (Daniel and Filho, 2007;Katayama et al, 2001).…”
Section: F Industrial Applicationsmentioning
confidence: 99%
“…Peptaibols have a mechanism of action similar to calcitonin, a hormone secreted by the thyroid gland in response to elevated levels of calcium in the blood that plays an important role in maintaining homeostasis (Katayama et al, 2001). Experiments with peptaibols demonstrate their ability to induce the secretion of catecholamines from chromaffin cells in the adrenal medulla by calcium influx; to activate adenylate cyclase and guanylate cyclase; to make the plasma membrane of mouse lymphocytes permeable to ATP, thereby allowing the adenylate cyclase activity of the cells to be determined; and to exert antitumor effects in hepatocellular carcinoma cells (Daniel and Filho, 2007;Katayama et al, 2001). The peptaibol trichokonins, from Trichoderma pseudokoningii SMF2, exhibited antibiotic activities against plant fungal pathogens.…”
Section: F Industrial Applicationsmentioning
confidence: 99%
See 1 more Smart Citation